2021
DOI: 10.3390/nu13010185
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status and Diet Style Affect Cognitive Function in Alcoholic Liver Disease

Abstract: Malnutrition and cognitive dysfunction are typical features of alcoholic liver disease (ALD) and are correlated with the development of complications. The aim of this study is to explore the effect of nutritional state and diet on cognitive function in ALD. A total of 43 patients with compensated alcoholic cirrhosis were enrolled, and a neuropsychological test was assessed according to body mass index (BMI, <22 and ≥22). In the ALD animal study, mice were divided into five groups (n = 9/group; normal liquid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The gut microbiota plays an ameliorative role in liver diseases. Liver diseases such as fatty liver, hepatitis, and cirrhosis are related to bile acid secretion disorder and metabolic syndrome ( 56 , 86 , 87 ). Table 3 lists the more important metabolites in the human gut microbiome.…”
Section: Gut Microbiota and One Carbon Metabolismsmentioning
confidence: 99%
“…The gut microbiota plays an ameliorative role in liver diseases. Liver diseases such as fatty liver, hepatitis, and cirrhosis are related to bile acid secretion disorder and metabolic syndrome ( 56 , 86 , 87 ). Table 3 lists the more important metabolites in the human gut microbiome.…”
Section: Gut Microbiota and One Carbon Metabolismsmentioning
confidence: 99%
“…19,20 Some women with anemia have poor nutritional status. 21 Lack of energy intake is one of the factors associated with anemia. 7 A study in a school in the city of Padang showed that the prevalence of anemia among adolescents was 49.1%.…”
Section: Introductionmentioning
confidence: 99%
“…The intestines and liver are, thus, the main organs that are damaged by alcohol. The pathogenesis of ALD is complex, and the existing treatment methods of abstinence, diet, and drug therapy for ALD have some drawbacks [ 6 , 7 , 8 ]. Therefore, exploring the pathogenesis of ALD to identify a suitable treatment for the disease is essential.…”
Section: Introductionmentioning
confidence: 99%